Relationships of Work Environment and Burnout among Perioperative Nurses in Spain - Sillero-Sillero, Amalia (Challenges in Disease and Health Research Vol. 7, 2021)
Background: Several international studies have documented a connection between nurses’ working environment and burnout. However, there are a paucity of studies have been conducted to date regarding perioperative nurses burnout and the characteristics of their working environments in Spain. Objective: To analyse the influence of organizational factors of the perioperative nurse`s work environment on the three-burnout dimensions: emotional exhaustion, depersonalisation, and personal accomplishment. Methods: We conducted a cross-sectional, quantitative, prospective study with 130 surgical nurses in a tertiary hospital in Spain using a self report questionnaire to data collect a socio-demographic, the Maslach Burnout Inventory, and the Practice Environment Scale of the Nursing Work Index. Analysis: A univariate and a bivariate analysis between organisational factors, explanatory variables and burnout dimensions were performed and, finally, a multivariate regression was used to ascertain the effect of the NWI-PES factors on burnout. Results: The degree of general burnout was moderate-high. This study showed emotional exhaustion in 43% (56) of nurses, depersonalization in 21% (28), and reduced personal accomplisment in 53 % (69). The work environment was considered unfavourable as only one factor of five was favourable (Nursing foundations of quality care). Multiple regression analyses showed three organizational factors were associated with all three dimensions of burnout: “Nurse manager ability, leadership, and support of nurses”; “Staffing and resources adequacy”; and “Nursing foundations of quality care”. Conclusions: Burnout prevalence in perioperative nurses is high-moderate and affects about one-third of the sample in each of the 3 burnout subscales — Emotional Exhaustion is the most affected subscale, followed by Depersonalization and Personal Accomplishment. In this study three organizational factors played a significant role in predicting burnout among perioperative nurses. We recommend hospital management implement policies to improve these organizational factors. Addition to interventions in the work environment, which has an important influence on burnout: Promoting positive leadership styles, providing necessary resources, and creating a positive climate in the work environment could increase psychosocial wellbeing and decrease burnout among perioperative nurses.